P236 Allergy services at a tertiary referral centre: a 1-year retrospective review of all referrals. (16th November 2010) - Swindlehurst, N L; Swindlehurst, A M; Kaul, S; Corrigan, C
Abstract : Introduction: A retrospective review was performed of all new referrals attending the Allergy Dept at Guys and St Thomas' NHS Foundation Trust (GSTT) over 12 months. The purpose was to establish the prevalence of non-allergic and allergic disease, determine the value of the investigations requested and ascertain the correlation between initial and final diagnoses. Method: All 1702 new patient referrals made to the allergy clinic between 1/01/2006 and 1/01/2007 were reviewed. Information collated included patient demographics, referral source, referral reason, working diagnosis, investigations requested, frequency of abnormal blood test findings, final diagnosis, and outcome after attending first appointment. Results: The age at presentation was 38±17 (Mean±SD). The female to male ratio was 3:1; the most common source of referral was primary care (84%); 54% of the working diagnoses after first consultation were allergic conditions, the commonest being food allergy; the final diagnosis was predominantly a non-allergic condition (65%), the commonest being idiopathic urticaria. Skin prick testing (65%) and full blood count (18%) were the commonest investigations requested with abnormal results recorded in 59% and 38%, respectively. 54% of the patients were discharged at first appointment and 26% were followed-up allergy out-patient appointments. The rest were referred to another speciality (5%) or to specialist services within the department (drug challenge (5%), dietician (4%), immunotherapy (4%), and food challenge (1%)). Diagnostic concordance data between referral sources and allergy specialists revealed that Emergency Department, Primary Care and Dermatology referrals were associated with a lower diagnostic agreement, (40%, 52% and 59%) respectively as compared to referrals from ENT and Immunology resulting in 86% diagnostic concordance. Overall there was a 57.5% and 92% agreement between the working and final allergic and non-allergic diagnoses respectively. Conclusion: The majority of new patient referrals seen in this Allergy Centre year did not have a final diagnosis of allergy. The diagnostic agreement between certain referral sources & allergy specialists was low providing a focus for targeting allergy educational resources. Training programmes should endeavour to produce specialists competent in the diagnosis and management of both allergic and non-allergic conditions which may share similar modes of presentation.